The Big-Man from the “White House.”: Negotiating Power in a Slovak Post-Rural Community - Bittnerová, Dana; Heřmanský, Martin; Novotná, Hedvika (Lidé města, 2010)
This paper deals with the issue of negotiating power and exerting authority in a contemporary post-rural community. It analyzes various strate¬gies of village representatives by which they build their influence and create obligations among the villagers. At the same time it shows how the village inhabitants deal with incurred moral and economical dependence on village representatives. The issue will be addressed through the lens of the dynamics of the rise and fall of the village’s main representative. The big-man theory, proposed by Marshall Sahlins, will be used as the explication framework.